Black and White Parents' Willingness to Seek Help for Children's Internalizing and Externalizing Symptoms. Issue 1 (16th June 2017) - Thurston, Idia B.; Hardin, Robin; Decker, Kristina; Arnold, Trisha; Howell, Kathryn H.; Phares, Vicky
Abstract : Objective: Understanding social and environmental factors that contribute to parental help‐seeking intentions is an important step in addressing service underutilization for children in need of treatment. This study examined factors that contribute to parents' intentions to seek formal and informal help for child psychopathology (anxiety and attention‐deficit/hyperactivity disorder [ADHD]). Method: A total of 251 parents (N = 128 mothers, N = 123 fathers; 49% Black, 51% White) read 3 vignettes describing children with anxiety, ADHD, and no diagnosis. Measures of problem recognition, perceived barriers, and formal (pediatricians, psychologists, teachers) and informal (religious leaders, family/friends, self‐help) help seeking were completed. Four separate hierarchical logistic regression models were used to examine parental help‐seeking likelihood from formal and informal sources for internalizing and externalizing symptoms. Predictors were socioeconomic status, parent race, age, and sex, parent problem recognition (via study vignettes), and perceived barriers to mental health service utilization. Result: Mothers were more likely than fathers to seek help from pediatricians, psychologists, teachers, and religious leaders for child anxiety and pediatricians, religious leaders, and self‐help resources for child ADHD. Black parents were more likely to seek help from religious leaders and White parents were more likely to use self‐help resources. Problem recognition was associated with greater intentions to seek help from almost all formal and informal sources (except from friends/family). Conclusion: Understanding factors that contribute to parental help seeking for child psychopathology is critical for increasing service utilization and reducing the negative effects of mental health problems. This study highlights the importance of decreasing help‐seeking barriers and increasing problem recognition to improve health equity.